Interactive spatial decision support system for supporting collaborative planning :Powerpoint - Flacke, J. (University of Twente, 2020)
This lecture presents: What is Spatial Decision Support System (SDSS)?; Conceptualizing Interactive Spatial Decision Support System: Three Forms of Interaction; Medium & Environment of Interaction; Research Aim; Spatial Context; Buzz word of 90s: Spatial Understanding Support System; SUSS Revisited: Interactive Spatial Understanding Support System.